Governance and Sustainability in Local Government - Anona Armstrong; Yongqiang Li (Australasian Accounting, Business and Finance Journal, 2022)
According to auditor reports in 2021, local government councils are failing their communities and their voters. Victorian Auditor General’s Office (VAGO) Reports 2021 suggest that the Councils of local governments are rife with conflicts of interest, manipulation of land deals, lacking independence and captured by their CEOs. The Victorian Government has recently introduced a new Local Government Act 2020 (VIC) to address the corruption, poor professional conducts of particular individuals and poor organisational culture exhibited by local government councils. The paper raises questions about what this will mean for local government governance, risk management and accountability, culture and leadership, relationships within councils, and how the inclusion of community governance will impact on the selection of and efficient delivery of programs. A fundamental challenge facing local government is determining the sustainable governance structures and practices that meet the needs of their communities in ways that balance economic, environmental, social and governance concerns. The paper draws on previous research that touch on ESG issues and identifies some areas for further research.
Keywords: ESG; sustainability; ethics; culture; governance; local government